2016
DOI: 10.2174/1567202613666160601144254
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 and TRPM8 Receptors May Promote Local Vasodilation that Aggravates Oxaliplatin-Induced Peripheral Neuropathy Amenable to 17β-Estradiol Treatment

Abstract: Oxaliplatin is a widely used chemotherapeutic agent that induces both acute and chronic peripheral neuropathy. Based on previous research indicating that estrogen replacement may attenuate some forms of pain in ovariectomized animals, we examined the effects of 17β-estradiol in OXAIPN. We discovered that local cold exposure induces an abnormal vascular response in both acute and chronic models of OXAIPN (oxaliplatin-induced peripheral neuropathy) that may be used as an easy and non-invasive method to predict w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Past research involving cold stress-induced detrusor overactivity revealed that the loss of estrogen due to ovariectomy increased expression of TRPM8 channel mRNA and cognate protein in lumbar skin [ 23 ]. Other recent studies also showed that OVX rats or mice with a long-term deficiency of estrogen exhibited greater sensitivity to thermal and mechanical stimuli, while estrogen replacement relieved such hyperalgesia [ 19 , 25 , 27 ]. This suggests that the TRPM8 channel may be overexpressed in dermal layers of postmenopausal women with low estrogen levels, who have symptoms of hypersensitivity to cold, and that estrogen replacement may improve the overexpression of TRPM8 channel mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research involving cold stress-induced detrusor overactivity revealed that the loss of estrogen due to ovariectomy increased expression of TRPM8 channel mRNA and cognate protein in lumbar skin [ 23 ]. Other recent studies also showed that OVX rats or mice with a long-term deficiency of estrogen exhibited greater sensitivity to thermal and mechanical stimuli, while estrogen replacement relieved such hyperalgesia [ 19 , 25 , 27 ]. This suggests that the TRPM8 channel may be overexpressed in dermal layers of postmenopausal women with low estrogen levels, who have symptoms of hypersensitivity to cold, and that estrogen replacement may improve the overexpression of TRPM8 channel mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al [ 8 ] reported that Icilin, a TRPM8/TRPA1 agonist, produces a dose-related hyperthermic response mediated by NO production in rats. Furthermore, Pan et al [ 25 ] reported that, in rats, TRPM8/TRPA1 promotes oxaliplatin-induced-vasodilation, which is associated with NO metabolites, and this vasodilation is attenuated by 17β-estradiol. Together with these reports, TRPM8 and estradiol seem to be related with mechanisms of thermosensation, involving vascular regulation mediated by NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen alters signal transduction and cellular activity by regulating the response of neurons to nociceptive receptors and ion channels (Chaban, 2012;Pan et al, 2016). The transient receptor potential ion channel (TRPV) and purinergic receptors (P2X2R and P2X3R) are known to participate in visceral nociceptive integration (Basbaum, 2009).…”
Section: Peripheral Modulation Of Visceral Pain Processing By Estrogenmentioning
confidence: 99%
“…The TRP family is broadly reflected in the nervous system. TRP vanilloid 1 (TRPV1), TRP vanilloid 2 (TRPV2), TRP vanilloid 3 (TRPV3), TRP vanilloid 4 (TRPV4), TRP ankyrin 1 (TRPA1) and TRP melastatin 8 (TRPM8), which belong to the large TRP ion channel superfamily, are critical contributors to normal and pathological pain [14,15] . Smith et al concluded that there was increased expression of TRPA1, TRPV1 and TRPM8 in DRG neurons [16] .…”
mentioning
confidence: 99%
“…Smith et al concluded that there was increased expression of TRPA1, TRPV1 and TRPM8 in DRG neurons [16] . Pan et al reported that the TRPM8 and TRPA1 expression were up-regulated in both acute and chronic pain [14] . Ceppa et al considered that TRPV4 could contribute to pain and TRPA1 might contribute to inflammation [15] .…”
mentioning
confidence: 99%